2000
DOI: 10.1128/iai.68.12.6807-6818.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Immunogenicity of Group AStreptococcusCulture Supernatant Proteins

Abstract: Extracellular proteins made by group A Streptococcus (GAS) play critical roles in the pathogenesis of human infections caused by this bacterium. Although many extracellular GAS proteins have been identified and characterized, there has been no systematic analysis of culture supernatant proteins. Proteins present in the culture supernatant of strains of serotype M1 (MGAS 5005) and M3 (MGAS 315) mutants lacking production of the major extracellular cysteine protease were separated by two-dimensional gel electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
1
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 54 publications
(56 reference statements)
9
141
1
3
Order By: Relevance
“…We postulate that increased expression of RsbU represents an attempt by S. pyogenes to activate the SigmaB stress response to cope with the effects of fluoride. Several examples are present in the literature of the application of proteomic analysis to the study of Streptococcus species (19,35,36). None of these studies examined the effect of fluoride on S. pyogenes and cannot be used to confirm our findings.…”
Section: Effect Of Fluoride On Protein Expression In S Pyogenes Cultcontrasting
confidence: 39%
“…We postulate that increased expression of RsbU represents an attempt by S. pyogenes to activate the SigmaB stress response to cope with the effects of fluoride. Several examples are present in the literature of the application of proteomic analysis to the study of Streptococcus species (19,35,36). None of these studies examined the effect of fluoride on S. pyogenes and cannot be used to confirm our findings.…”
Section: Effect Of Fluoride On Protein Expression In S Pyogenes Cultcontrasting
confidence: 39%
“…Assessment of in Vitro Production of SlaA-GAS strains used to test for in vitro production of SlaA were cultured in protein-reduced ToddHewitt broth containing 0.2% (w/v) yeast extract (PR-THY; Difco Laboratories, Detroit, MI) in 5% CO 2 at 37°C (20). Bacteria were grown to mid-exponential, early stationary phase, and overnight, centrifuged, and the pellet was discarded.…”
Section: Methodsmentioning
confidence: 99%
“…These authors also demonstrated considerable cross-protection of the 30-valent vaccine against non-vaccine M serotypes [4]. Recently, a series of independent studies have documented a class of GAS cell wall-associated or secreted metabolic enzymes that contain neither N-terminal leader sequences nor C-terminal cell wall anchors [5][6][7][8][9]. Perhaps because these molecules do not fit common categories of bacterial vaccine antigen, e.g.…”
mentioning
confidence: 99%